KOMODIFIKASI DALAM AJANG PENCARIAN BAKAT PENYANYI DANGDUT LIGA DANGDUT INDONESIA DI INDOSIAR - Kurniawan, Kurniawan; Nupus, Hayati (Universitas Prof. Dr. Moestopo (Beragama), 2020)
Liga Dangdut Indonesia (Indonesian Dangdut League) is a popular dangdut singer talent contest in Indosiar television station. It is part of the media strategy to gain ratings and audience share to compete for a slice of the limited advertising cake in the free-to-air commercial television broadcasting. This competiton encourages television managers to think hard to create flagship programs that become media commodities to attract viewers and advertisers. This study aims to identify some forms of commodification on Liga Dangdut Indonesia. Study of dangdut is important for communication research because it will help more understanding about the modern nation-state culture of Indonesia. Drawing on a critical political economy framework, this study uses Mosco's theory regarding processes of commodification of media content, audiences, and workers. Researchers added Fuchs's theory of digital workers to see the phenomenon of commodification in the digital age. This is a qualitative research with case study method. Data collection techniques are carried out by observation and interviews as well as exploring news, audiovisual material, and reports. Researchers found that commodification occurs in the contest in the form of the commodification of media content, audiences, workers, and digital workers. This commodification hides exploitative social relations by presenting them in a form that mistifies dangdut as global, upper-class, nobel culture.